Analisis Penerimaan Teknologi Cloud Storage Menggunakan Technology Readiness Acceptance Model (TRAM) Pada Badan Eksekutif Mahasiswa Institut Teknologi Sepuluh Nopember - Hannah Rosmayanti; Himawat Aryadita; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The objective of cloud storage technology are improve the operational of an organization to achieve the expected objective. Badan Eksekutif Mahasiswa Institut Teknologi Sepuluh Nopember (BEM ITS) is the executant of student activities of the level of institute. Cloud storage technology is the technology that allows the user to process data and saving data on cloud or online. TRAM is a model combined of personality dimension from Technology Readiness Index (TRI) and technology dimension from Technology Acceptance Model (TAM). The population of this research is all members of BEM ITS. And the sample of this research is same with the population. This research using non-probability sampling with the technique using total sampling. Data collected through the spreading of questionnare online to 260 members of BEM ITS. This analysis method using Structural Equation Modeling (SEM). The optimism of members has a positive and significant influence with the perceive usefulness and perceive ease of use. Innovativeness has a positive and significant influence with the perceive usefulness but not significant with perceive ease of use. Then, insecurity has a negatively and significantly influences with the perceive usefulness but not with perceive ease of use. Discomfort has no influence on perceive usefulness. Then, the perceive ease of use factor has a positive and significant influence with perceive usefulness.